Analisis Perwilayahan Komoditas Kopi - Ari Septianingtyas Purwandhini; Endang Wahyu Pudjiastutik; Nuril Exwin Suhaeriyah (Hasanuddin University, 2023)
Abstract In 2020 Jember Regency is one of the regencies contributing the most coffee production in East Java with a total production of 236,899 tonnes. Out of a total of 31 sub-districts in the Jember Regency, 16 sub-districts do not produce coffee, while the remaining 15 sub-districts produce coffee with yields varying from 0.018 tons to 78.858 tons. Based on 2020 BPS data, the largest production was in the Silo District 78,858 tons. This study aims to determine: 1) the trend of coffee production in Jember Regency; 2) which areas in Jember Regency are coffee production bases; 3) is the distribution of coffee localized or specialized in coffee-producing areas in Jember Regency. The method used is descriptive and correlational with purposive sampling. The results of the study show that: 1) forecasting the development of coffee commodities in Jember Regency shows an increasing trend of coffee production in 2021-2024. The development of coffee commodity production in Jember Regency shows a positive value, meaning that coffee production tends to increase from year to year; 2) the sub-districts that are the basis for the coffee commodity in Jember Regency from a production point of view include the sub-districts of Arjasa, Bangsalsari, Jelbuk, Ledokombo, Panti, Patrang, Silo, Sukorambi, Sumberbaru, Sumberjambe, and Tanggul; (3) the distribution of coffee commodities in Jember Regency based on localization analysis shows that the coffee plantation business is not concentrated in one area, but spreads out in several areas of Jember Regency. Meanwhile, for the analysis of coffee commodity specialization in the Jember Regency, several sub-districts have specificities in an area. Keywords: coffee; regional analysis; forecasting.